EFEKTIVITAS MEDIA KOMIK TERHADAP PENINGKATAN PENGETAHUAN DAN SIKAP PELAJAR SEKOLAH MENENGAH ATAS DI PERKOTAAN PADA SWAMEDIKASI DEMAM - ., Mykle Jeky Lala (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2015)
Self medication is defined as usage of drugs in community to relieve symtomps of minor illnesses without doctor intervention. Health education can bedone using comic. Comic is the mass media that using a colourfull picture includethe texts for carrying the information. The research design was a quasyexperimental design with one group pretest-posttest design. The samples in thisstudy were 30 respondents as experiment group from SMAN 3 Singkawang usepurposive sampling tehnique. Research instrument use questionaires and comic.The results of the study use statistic analyze by using paired sample t-test test witha value of Î±= 0,05 that showed on experiment groupÂ  the comic was effective forknowledge improvement (p = 0,007) and for attitude improvement (p = 0,000).Keyword : self medication, health education, comic